1998
DOI: 10.1377/hlthaff.17.6.181
|View full text |Cite
|
Sign up to set email alerts
|

Can Medicare Beneficiaries Make Informed Choices?

Abstract: This DataWatch assesses Medicare beneficiaries' understanding of the differences between their managed care and fee-for-service Medicare options. A telephone survey was used to evaluate knowledge levels among 1,673 beneficiaries residing in five Medicare markets with high managed care penetration. Half of the sample were enrolled in health maintenance organizations (HMOs) and half in the traditional Medicare program. The findings show that 30 percent of beneficiaries know almost nothing about HMOs; only 11 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 6 publications
4
86
0
5
Order By: Relevance
“…Numerous studies have shown that individuals incorrectly report enrollment in a managed care plan and misunderstand managed care definitions and practices (Hibbard et al 1998;Miller and Horowitz 2000;Flores et al 2004). This proxy of managed care coverage has been previously used and in the absence of administrative data is a more accurate way of identifying managed care enrollment than directly asking individuals.…”
Section: Notesmentioning
confidence: 99%
“…Numerous studies have shown that individuals incorrectly report enrollment in a managed care plan and misunderstand managed care definitions and practices (Hibbard et al 1998;Miller and Horowitz 2000;Flores et al 2004). This proxy of managed care coverage has been previously used and in the absence of administrative data is a more accurate way of identifying managed care enrollment than directly asking individuals.…”
Section: Notesmentioning
confidence: 99%
“…A possible explanation for these findings is that having more plans available in a market is related to greater plan visibility among beneficiaries and members of their support systems due to marketing or if having more plans provides broader provider participation in Medicare managed care. Beneficiaries rely on plan materials, friends and family, and their physician as important sources of information and advice (Gold et al, 2000;Hibbard et al,1998), and their physician's participation in a plan network is a critical part of considering managed care options (Gold et al, 2000;Scanlon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…В Иллинойсе, например, страховщики обязаны обнародовать все суммы оплаты помимо страховой премии 45 . Законы о финансирова-нии страховок требуют сообщать о способах оплаты страховки со стороны клиентов 46 . Требуется также сообщать о страховых продуктах с инвестиционными рисками 47 .…”
Section: страхованиеunclassified